Study on the Durability of Graphene Oxide–Nanosilica Hybrid-Modified Sticky Rice–Lime Paste - Ke Li; Donghui Cheng; Yingqi Fu; Xuwen Yan; Li Wang; Haisheng Ren (Nanomaterials)
In order to improve the durability performance of sticky rice–lime paste in ancient masonry restoration materials, the effect of graphene oxide–nanosilica hybrids (GO–NS) on its basic physical properties and durability performance was investigated. The surface morphology, physical phase characteristics and infrared spectra of GO–NS and its sticky rice–lime paste were analysed by SEM, FE-TEM, XRD and FTIR. It was shown that NS successfully attached to the GO surface and improved the interlayer structure of GO. GO–NS reduces the fluidity and shrinkage of sticky rice–lime paste, prolongs the initial setting, shortens the final setting and significantly improves the compressive strength, water resistance and freeze resistance. As NS improves the interlayer structure of GO, it provides nucleation sites for the hardening of the sticky rice–lime paste, improves the quantity and structural distribution of the hardening products and reduces the pores. The NS undergoes a hydration reaction with Ca(OH)2 in the lime to produce calcium silicate hydrate (C–S–H), which further refines the internal pore structure of the sticky rice–lime paste. As a result, the GO–NS-modified sticky rice–lime paste has a denser interior and better macroscopic properties.